2021
DOI: 10.1093/mnras/stab2083
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the shadows of giants – II. The effect of local ionization on the Ly α absorption signatures of protoclusters at redshift z ∼ 2.4

Abstract: Local variations in the intergalactic medium (IGM) neutral hydrogen fraction will affect the Ly-α absorption signature of protoclusters identified in tomographic surveys. Using the IllustrisTNG simulations, we investigate how the AGN proximity effect and hot, collisionally ionised gas arising from gravitational infall and black hole feedback changes the Ly-α absorption associated with Mz = 0 ≃ 1014 M⊙ protoclusters at z ≃ 2.4. We find that protocluster galaxy overdensities exhibit a weak anti-correlation with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 98 publications
(168 reference statements)
0
10
0
Order By: Relevance
“…Recently, Miller et al (2021) analyzed proto-clusters in the Illustris TNG100 hydrodynamical simulation and studied the effect of AGN on the thermal and ionisation properties. They found that the AGN affects the Lyα transmission within ∼ 1 h −1 Mpc of the central halo at z ∼ 2.4, but the effects are minor when smoothed over the ≥ 4 h −1 Mpc scales typically used to search for proto-clusters in the Lyα forest.…”
Section: Cluster Halo Idmentioning
confidence: 99%
“…Recently, Miller et al (2021) analyzed proto-clusters in the Illustris TNG100 hydrodynamical simulation and studied the effect of AGN on the thermal and ionisation properties. They found that the AGN affects the Lyα transmission within ∼ 1 h −1 Mpc of the central halo at z ∼ 2.4, but the effects are minor when smoothed over the ≥ 4 h −1 Mpc scales typically used to search for proto-clusters in the Lyα forest.…”
Section: Cluster Halo Idmentioning
confidence: 99%
“…This is expected to have a mild effect on the protocluster signal in most cases. 48 More importantly, it can only reduce the observed absorption, and thus cannot account for our main result, the low galaxy density observed around the strongest absorption peaks. The same comment applies to any "pre-heating" of the intracluster medium 49 beyond the feedback implemented in TNG.…”
Section: Methodsmentioning
confidence: 69%
“…This requires radiative transfer simulations, which are computationally demanding. However, Miller et al (2021) placed an approximate bound on this effect by sampling the AGN luminosity function and assigning AGNs to massive halos in a one-to-one rank order fashion (implying a duty cycle of one). They conclude local ionization usually has a small effect on the Lyα absorption observed in tomographic maps, even within massive protoclusters.…”
Section: Summary and Discussionmentioning
confidence: 99%